Disrupting complacency: Helping students find their voices through inquiry, literature, and technology. Issue 5 (19th October 2016) - Seglem, Robyn; Bonner, Sarah
Abstract: This article highlights an inquiry project in an eighth-grade ELA class in a rural middle school. Using the novel Monster by Walter Dean Myers, we encouraged students to form questions relating the text to the larger world. To begin the unit, students participated in three anchor activities over a three-week period. Students blogged about the book, located non-fiction articles that connected to the text, and interviewed community members who shared roles similar to the characters in the novel. Then, through Socratic Seminar discussions and teacher questioning, we guided students toward the development of questions that emerged while reading the novel. Students researched their questions, refined their questions, and developed a campaign designed to educate their school about their findings. In addition to describing the inquiry process students engaged in, we demonstrate technology's role in the research process and in the production of texts that showcased their learning.